INVESTIGATION OF STRUCTURAL PROPERTIES OF DUST FORMATIONS IN COMPLEX PLASMA ON THE BASIS OF SPATIAL DENSITY SPECTRUM ANALYSIS - Daniyarov, T. T.; Ramazanov, T. S.; Jumabekov, A. N.; Zhankarashev, Ye. B.; Dosbolayev, M. K. (Recent Contributions to Physics, 2009)
In this paper, application of analysis of spatial density spectrum on the basis of two-dimensional Fourier transformation to the investigation of structural properties of macroscopic dusty formation in complex plasma is studied. The ability of this method to reveal hidden symmetry in the system is shown. This property rectifies its application to further study of real-time dynamics of phase transitions in dusty plasma.